The Role of Mechanically-Activated Ion Channels Piezo1, Piezo2, and TRPV4 in Chondrocyte Mechanotransduction and Mechano-Therapeutics for Osteoarthritis - Gao, Winni; Hasan, Hamza; Anderson, Devon E.; Lee, Whasil (Frontiers in Cell and Developmental Biology, 2022)
Mechanical factors play critical roles in the pathogenesis of joint disorders like osteoarthritis (OA), a prevalent progressive degenerative joint disease with debilitating pain. Chondrocytes are responsible cells for extracellular matrix (ECM) turnover, and mechanical stimuli heavily influence cartilage maintenance, degeneration, and regeneration via mechanotransduction of chondrocytes. Thus, understanding the disease-associated mechanotransduction mechanisms can shed light on developing effective therapeutic strategies for OA through targeting mechanotransducers with mechanotherapeutics to halt progressive cartilage degeneration. Mechanosensitive Ca2+-permeating channels are robustly expressed in primary articular chondrocytes and trigger force-dependent cartilage remodeling and injury responses. This review discusses the current understanding of the roles of Piezo1, Piezo2, and TRPV4 mechanosensitive ion channels in cartilage health and disease with a highlight on the potential mechanotheraputic strategies to target these channels and prevent cartilage degeneration associated with OA.